Examining women’s choice between home and institutional births: Insights from the Salud Mesoamérica Initiative (SMI) - Lucía Bartolomeu; Natalia Basualdo; Federico Rolón; Adolfo Rubinstein; Camila Volij; Matt Simon; Brittany Hagedorn; Diego Ríos-Zertuche; Santiago Esteban; Adrián Santoro (PLoS ONE, 2026)
This study examines women’s childbirth choices between home and institutional settings in the context of the Salud Mesoamérica Initiative, a results-based financing program focused on disadvantaged populations. This study characterizes the childbirth experience using the World Health Organization’s Positive Childbirth Experience framework, identifies factors influencing women’s decisions for home versus institutional births, and describes reasons for transitions between these settings, especially for women with multiple pregnancies. A retrospective observational study was carried out using secondary data from household surveys carried out in Guatemala, Chiapas (Mexico), Nicaragua, and Honduras. A two-stage random sample of women (15–49 years) who had a live birth within five years preceding the surveys was analyzed. Quality of institutional care and reasons for home birth were categorized into specific domains and data across three follow-up points were analyzed using design-adjusted chi-squared tests (Rao-Scott correction). Finally, for the second follow-up, a sub-analysis explored setting transitions for women with multiple pregnancies. The main results indicate that Guatemala had the highest rate of home births (83.8%), while institutional deliveries were more common in Honduras and Nicaragua. Over time, institutional births increased across the board, notably in Honduras, where they surged from 72.3% to 92.7%. The primary factors influencing birth setting choices were accessibility and cultural preferences, with the latter being particularly significant in Guatemala and Chiapas. The results underscore the critical need for culturally sensitive strategies to boost institutional birth rates. While enhanced accessibility has contributed to more institutional deliveries, deep-seated cultural preferences remain a considerable hurdle. Interventions that respect local beliefs while simultaneously improving the quality of care in institutional settings are essential to ensure safe childbirth for all women.